(untitled) (International Journal of Engineering and Computer Science, 2017)
Image processing plays a vital role in aspects of all science and technology.In this image processing concepts have great impotance in application oriented research and project.The purpose of the proposed research work is develop a computer system that can recognize a personization by comparing the characteristices of face to those of known individual.Human face recognition is an effective means of authenticating a person.Principal Component Analysis( PCA )is a classical feature extraction and data representation technique widely used in pattern recognition.It is most successful techniques in face recognition. Prototype is designed to work with web cameras for the face detection and recognizing system based on visual 2010 C#, and OpenCV.The proposed method have been evaluated using the Microsoft cognitive service API with Azure API of databases.This system can implement a better security of computational time to detect and recognize the human faces with big database